The Influence of STAD Method Towards Students Writing Ability in Recount Text - Adella Ramadhanti; Eva Nurchurifiani; Amelia Octafiyana; Anisa Safitri; Lusi Purnama Sari; Tommy Hastomo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The purpose of this research is to determine the influence of learning using the STAD method on students' writing ability. The researchers used quantitative and experimental research methodology. The researchers used two classes as samples, which consisted of an experimental and a control class. Students in the experimental class were provided with instruction with the STAD method, and students in the control class comprised instructed using conventional methods. In collecting data, the researchers used written tests.The ttest formula is used to analyze data throughout the research and obtain the results was ttest > ttable with a significance level of 0.05 and 0.01 (2.00 < 3,79 > 2.66). It can be concluded that there is an influence of using STAD method on students' writing ability. In addition, it was also found the average score in the experimental class was higher than the control class (72,29 > 63,81). Through this research, it can conclude that implementing of STAD method in teaching and learning English can rise students writing skill.